A phenomenological approach to psychological treatment for the multidisciplinary care of chronic back pain - F, Cecchi (International Journal of Psychosocial Rehabilitation, 2013)
psycho-social model and to recent theories of emotions. This paper aims at providing a systematic description of a psychological inter- vention based on a phenomenological approach within the multidisciplinary treatment ofCBP.Methods. Starting form the theory of disfunction in CBP and the theory of treatment, we describe here the theoretical framework and process components of a short-term, emotionally focused psychological intervention, to explain the choice we made to use a phenomen- ological approach to illness and pain, in terms of group context into the patients’ rehabilitation care pathway.Conclusions. A phenomenological approach within the multidisciplinary treatment of CBP aims at the recognition of the subjective ex- perience of illness, emotions associated to the illness and individual ways to communicate pain, with the ultimate intended outcome of relieving pain-related psychological distress and improving pain management. A systematic description of this approach may facilitate its integration in clinical practice.